Lexical Creativity in Thai English Fiction - Bennui, Pairote (Archīum Ateneo, 2024)
Unlike some varieties of English in Southeast Asia, the notion that there is a ‘Thai English’ is debatable. This paper examines distinctive non-native features of a lexicon found in contemporary Thai writing in English to ascertain if English in this Expanding Circle country is developing its own linguistic norms. An analysis of features of lexical creativity in five short stories and novels is carried out to determine whether the characteristics found indicate that a Thai English vocabulary exists. An ‘integrated framework’ which combines concepts in World Englishes by Braj B, Kachru, Peter Strevens, and Edgar W. Schneider is adopted in this study. It appears that certain categories of lexical creativity in the fiction examined represent five indicators of Thai English - contextualization, innovation, nativization, transcultural creativity, and localization - and reveals a developing non-native variety of English.